The relationship between adherence of internal audit with standards and audit fees. Issue 1 (4th July 2016) - Alzeban, Abdulaziz; Sawan, Nedal
Abstract : Purpose: This study aims to examine the relationship between external audit fees and the adherence of internal audit with the International Standards for the Professional Practice of Internal Auditing (ISPPIA), i.e. whether such adherence has a relation with lower or higher audit fees. Design/methodology/approach: Data were gathered from the annual reports and 229 chief internal auditors (CIAs) from UK companies listed on the London Stock Exchange. Findings: The result suggests that, in fact, higher external audit fee is related with adherence with both attribute and performance standards. Also, there is an association between audit fees and budget for the internal audit with longer tenure of the CIA. Originality/value: Given the lack of attention to the potential impact of the ISPPIA on audit fees by previous researchers, any insight provided by the study in this regard will represent a valuable contribution to the literature in complementing what already exists and pointing the way to further research opportunities.